PEMIKIRAN NEO-SUFISME - Otoman Otoman (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract:Neo-Sufism can be regarded as a reaffirmation effort Islamic values kaffah ( intact ), namely life tawazun ( berkeseimbangan ) in all aspects of life and in terms of human expression. Neo-Sufism has prompted the opening of opportunities for the appreciation of religious significance and its practice is more intact and not limited to just one aspect, but balanced. Supposedly every Muslim should recognize and realize the importance of the spiritual in Islam, but also keep in mind that the Quran states this is the real world not a mirage, nor maya without meaning. In principle Neo-Sufism has three things: First, al-Quran and al-Hadith. Second, make the Holy Prophet and salafi generation as a role model. Third, tawazun ( principle balance ) in Islam. The third principle is then supported by some anomaly in a fundamental reconstruction of Sufism and Sufi discourse formulation for the development of the concept of Neo-Sufism. Reconstruction and dynamics that include substantial essence of Sufism or ontological dimension, in this case related to three important things, which is substantially and methodologically, what is the source and means of acquisition (epistimologisnya aspects), as well as the function of Sufism, or axiological aspect. Thus, this article will discuss the nature of Neo-Sufism and thoughts related to the reconstruction effort, formulation and dynamic discourse of Sufism in the development of the concept. Keywords: Thoughts and Neo-Sufism